A nonlinear ultrasonic modulation approach for the detection and localisation of contact defects. (1st January 2022) - Andreades, Christos; Malfense Fierro, Gian Piero; Meo, Michele
Highlights: An ultrasonic phased array technique based on nonlinear modulation of elastic waves. Through-thickness inspection of metallic and composite materials. Identification/localisation of contact-type defects at multiple material interfaces. Higher sensitivity/accuracy relative to the conventional linear phased array method. Abstract: Critical metallic and composite structures are periodically inspected for contact defects such as kissing bonds and delamination, using phased array techniques based on linear ultrasound. The detection of contact flaws at multiple depths in the material can be challenging due to high signal attenuation and noise level. In this study an alternative ultrasonic phased array approach relying on the nonlinear modulation of dual-frequency excitation was introduced to improve the sensitivity and accuracy in the detection of contact defects. A phased array probe was used for the generation of single-frequency and dual-frequency waves, and the capturing of echoes. The flaws were detected using a new nonlinear modulated parameter characterising the response of the material arising only from the modulation sidebands at the sum and difference frequencies f2 +f1 and f2 -f1 . Ultrasonic tests were conducted on materials with multiple contact interfaces. The novel parameter was plotted against the linear response, and the peaks indicating the contact interfaces were compared based on their signal-to-noise ratio ( SNR ), their width at half-height (6 dB drop) and their positioning error. The peaks of the nonlinear modulated parameter offered up to 10 3 times higher SNR, up to 10 times smaller width at half-height and around 45% smaller localisation error than the peaks in the classical linear ultrasonic response. The results showed that the proposed approach could lead to more effective detection and more accurate localisation of contact defects in structural materials such as kissing bonds and closed delamination.